Lock cylinder and key - LIU XIAOJUN; FANG SICONG; ZENG GUOHUI (2023)
The utility model relates to the technical field of lock cylinders, and discloses a lock cylinder and a key, comprising: a lock case which defines a cavity, the lock case comprises a first locking part and a second locking part, and the first locking part and the second locking part are located on the inner wall of the lock case; the core body is rotatably arranged in the cavity, a channel is formed in the axial direction of the core body, and a key can be inserted into the channel; the blade device is movably arranged on the core body, the extension direction of the blade device is crossed with the channel, and the blade device can enter or retreat from the first locking part to lock or unlock the lock shell and the core body; and the authorization device is movably arranged on the core body and located in the extending direction of the channel, and at least part of the authorization device can enter or retreat from the second locking part to lock or unlock the lock shell and the core body. According to the